Effect of Arbuscular Mycorrhiza Fungi on Yield and Yield Components of Common Bean (Phaseolus vulgaris L.) and Dill (Anethum graveolens L.) in Mono and Intercropping System - Weria weisanny (Journal of Agricultural Science and Sustainable Production, 2016)
The effect of intercropping and arbuscular mycorrhizal fungi (AMF) on yield and yield components of common bean (Phaseolus vulgaris L.) and dill (Anethum graveolens L.), examined by a field experiments with a factorial arrangement based on randomized complete block design with three replications in Agricultural and Natural Resources Research Center of Kurdistan. The first factor, cropping systems including sole cropping of common bean (40 plant.m-2), sole cropping of dill with density of 25, 50 and 75 plant.m-2, additive intercropping including 75, 50 and 25 plant.m-2 to 40 plant/m2, and the second factor, AMF including with and without (control) AMF application. The results showed that additive intercropping increased dill seed yield. In common bean, intercropping increased the weight and number of pod and seed yield. Whereas, intercropping, compared whit sole cropping reduced the number of umbels and umbelets, branches per plant. AMF application significantly increased the number of umbels, umbelets and branches per plant and seed yield. Also, in common bean, AMF significantly increased weight and number of pod and seed yield.  Relative yield total (RYT) and relative value total (RVT) for most of the intercropping combinations were greater than one, which indicates the superiority of intercropping to monoculture.